ANALISIS PENCEGAHAN BENCANA DI KAWASAN PULAU BADI - Ainun Jariah; Salsa Fitrah (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Badi Island is a small island in the Spermonde island cluster in the waters of the Makassar Strait. It is included in the administrative areas of Pankajene and Islands Regency, Liukang Tupabiling District, and Mattiro Dechen Village in Indonesia, South Sulawesi. A tornado hit Buddy Island in 2019, and a lot of household trash was dumped on the beach. Mitigation measures are one way to reduce the effects of disasters. Disaster management on Badi Island, which is part of the Regional Marine Conservation Area of Pankajen Island Regency and Islands, is carried out by the Regional Disaster Management Agency of Pankajene Island Regency. This study aims to gain a better understanding of how natural disasters can be mitigated on Badi Island by considering the context of the community. Where a comprehensive understanding of natural disaster mitigation on the fragile island is still lacking. The number of disasters that occur is very high. Disasters can happen at any time. Analytical descriptive research methods were used in this study. Results show that many programs and activities are not implemented, as well as poor planning, disaster preparedness education, and lack of response from authorities. In addition, the most significant operational barriers are inadequate human resources, lack of infrastructure and equipment, limited capital, driven by a lot of external support, and lack of equipment and infrastructure.